KONSEPSI POLITIK SARINAH SEBAGAI POLITIK PEMBEBASAN Studi Pada Kebangkitan Perempuan Banyuwangi dalam Politik Lokal - Pratiwi, Sulistia; Bahri, Subur; Priyanto, Hary (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2021)
Abstract: The Conception of Political Sarinah As Political Freedom; A Study of The Banyuwangi Women ’s Emancipation at Local Politics . Political Sarinah as political freedom is a strategy and an act which are done by the women to change patriarchy view that attach on them. Thus, the Banyuwangi women are able to rise up as a leader. The purpose of this study were to identify and describe the strategy of the women ’s emancipation in order to get authority at the Banyuwangi Government. This research was descriptive qualitative research and the data collection was conducted through observation, interview (semi-structured interview) and documentation. Moreover, the result of the study showed that the women ’s political strategy in Banyuwangi was based on eight aspects. First, the planning aspect, which was they had a perfect plan before they joined political social field. Second, the organizing aspect, which was they had been trained themselves by joining organization. Third, the actuating aspect, which was they implemented their victory strategy persistently and systematically. Fourth, the controlling aspect, which was they did not do supervisory optimally. Fifth, the strengths aspect, which was they tended to be ambitious with their ability. Sixth, the weakness aspect, which was men tended to be disagree with women ’s leader. Seventh, the opportunities aspect, which was the Banyuwangi women had been educated and experienced. The last, threaten aspect, which was the Banyuwangi men acknowledged women ’s politic so there was no threat for women ’s leader.